Thyroid blood flow in inferior thyroid artery as predictor for increase in levothyroxine dosage during pregnancy in women with Hashimoto's thyroiditis - a retrospective study - Masafumi Kurajoh; Akiyo Yamasaki; Toshiki Nagasaki; Yuki Nagata; Shinsuke Yamada; Yasuo Imanishi; Masanori Emoto; Kanae Takahashi; Kouji Yamamoto; Ayumi Shintani; Masaaki Inaba (BMC, 2019)
Abstract Background We examined whether inferior thyroid artery peak systolic velocity (ITA-PSV) predicts an increase in levothyroxine (LT4) dosage in pregnant women with Hashimoto's thyroiditis. Methods Twenty-two women with Hashimoto's thyroiditis who were planning and later achieved pregnancy or confirmed as pregnant were enrolled in this retrospective longitudinal observational study. ITA-PSV and thyroid volume were measured using ultrasonography. Serum concentrations of free thyroxine (F-T4), free triiodothyronine (F-T3), and thyroid stimulating hormone (TSH) were simultaneously determined. We adjusted LT4 dosage to maintain serum TSH at < 2.5 μIU/mL (1st trimester) and later at < 3 μIU/mL (2nd, 3rd trimester). Results Eighteen patients (81.8%) required an increase in LT4 dosage during pregnancy, of whom 7 (31.8%) required an increase ≥50 μg. Multivariable regression analysis showed that TSH (β = 0.507, p = 0.008) and ITA-PSV (β = − 0.362, p = 0.047), but not thyroid volume, F-T4, or F-T3, were independently associated with increased LT4 dosage. Receiver-operating characteristic analysis for predicting an increase in LT4 ≥ 50 μg/day showed that the area under the curve (0.905) for ITA-PSV with TSH was not significantly increased (p = 0.123) as compared to that (0.743) for TSH alone, whereas integrated discrimination improvement was significantly increased (27.9%, p = 0.009). Conclusions In pregnant patients with Hashimoto's thyroiditis, ITA-PSV was a significant predictor of increase in LT4 dosage independent of TSH level, while ITA-PSV plus TSH showed significantly improved predictability as compared to TSH alone. These results suggest that ITA-PSV reflects residual thyroid function and is useful for evaluating the need for increased thyroid hormone production in pregnant patients with Hashimoto's thyroiditis.